Distribusi Vektor Filariasis Paska Transmission Assesment Survey Pertama (TAS-1) di Kabupaten Donggala - Made Agus Nurjana; junus widjaja; yuyun srikandi; Risti Risti (Jurnal Vektor Penyakit, 2021)
ABSTRACT First Transmission Assessment Survey (TAS-1) has been carried out successfully in Donggala District. The success was supported by epidemiological aspects, including data on the presence of vectors and the environment that is potential as a breeding places for mosquitoes. In order for Donggala District to achieve filariasis elimination formally, it is important to determine the existence of vectors and itspotential environment so as to continuously control them instead of other epidemiological interventions. A cross-sectional study was conducted to determine the presence of post-TAS-1 vector in Donggala District Activities include mosquito surveys and environmental surveys in two selected locations, namely Kelurahan Kabonga Kecil, Kecamatan Banawa and Sabang Village, Kecamatan Dampelas Donggala District. The results showed that 2,978 mosquitoes were caught from the genera Mansonia, Culex, Aedes, Anopheles, Armigeres, Uranotaenia, Coquilettidia and Aedomvia, the results of PCR examination showed mosquitoes were negative Brugia malayi. The mosquitoes” habitats were tree holes, ponds, rice fields, used goods, post -mining excavations, rivers, waterways, puddles, swamps, ponds, dug holes, springs, boats, water reservoirs, used tires, wells, coconut shells, and used cans. Monitoring and evaluation of program implementation by the local government, including routine vectors and environmental monitoring, must be continued as to maintain the elimination status of filariasis in Donggala District. ABSTRAK Transmission Assessment Survey pertama (TAS-1) telah dilakukan di Kabupaten Donggala dan dinyatakan lulus. Keberhasilan didukung oleh aspek epidemiologi di antaranya adalah data keberadaan vektor dan lingkungan yang potensial sebagai tempat perkembangbiakan nyamuk. Agar Kabupaten Donggala mencapai eliminasi filariasis maka keberadaan vektor dan lingkungan yang potensial dapat dikendalian disamping intervensi terhadap aspek epidemiologi lainnya. Studi potong-lintang dilakukan untuk mengetahui keberadaan vektor paska TAS-1 di Kabupaten Donggala. Kegiatan meliputi survei nyamuk dan survei lingkungan di dua lokasi terpilih yaitu Kelurahan kabonga Kecil, Kec. Banawa dan Desa Sabang, Kec. Dampelas Kabupaten Donggala. Hasil penelitian menunjukkan bahwa nyamuk tertangkap sebanyak 2.978 ekor dari genus Mansonia, Culex, Aedes, Anopheles, Armigeres, Uranotaenia, Coquilettidia dan Aedomvia, hasil pemeriksaan PCR menunjukkan nyamuk negatif Brugia malayi. Lingkungan habitat nyamuk yaitu: lubang pohon, kolam, sawah, barang bekas, bekas galian tambang, sungai, saluran air, genangan air, rawa, tambak, lubang galian, mata air, perahu, penampungan air, ban bekas, sumur, batok kelapa, dan kaleng bekas. Monitoring dan evaluasi pelaksanaan program oleh pemerintah daerah termasuk pemantauan vektor dan lingkungan secara rutin harus terus digalakkan agar status eliminasi filariasis di Kabupaten Donggala dapat dipertahankan.